Workplace Mental Health in Correctional Institutions: A Conceptual Narrative Analysis in Kerala - Reju T; Krishnamurthy V.S; Niviya Feston (Journal of Psychology and Social Sciences, 2026)
Correctional officers perform high-risk, demanding public safety functions involving the simultaneous supervision of incarcerated offenders, preservation of institutional order, enforcement of human rights protections, and execution of offender rehabilitation programs. Sustained hypervigilance, volatile interpersonal conflicts, irregular night schedules, systemic understaffing, and acute emotional labor expose prison personnel to heightened risks of psychological distress, chronic fatigue, and occupational burnout. Despite significant progressive prison reforms in post-independence India focusing on inmate welfare and humane custodial management, research evaluating the workplace mental health of correctional staff remains scarce. This study provides a conceptual narrative analysis of the occupational and psychological stressors experienced by correctional personnel in Kerala using an illustrative Composite Vignette methodology. Grounded in the Job Demands–Resources (JD–R) model and Conservation of Resources (COR) theory, empirical literature and official reports—including NIMHANS data and international correctional studies—were qualitatively synthesized. The analysis identifies eight primary occupational and psychological challenges: chronic hypervigilance, sleep disturbances, internal emotional exhaustion, interpersonal detachment, work–life conflict, help-seeking stigma, repeated exposure to unaddressed trauma, and a compulsory sense of duty under structural constraints. To protect personnel well-being and maintain institutional security, prison administrations must implement systemic reforms, including structured 8-hour shift rotations, institutional mental health education, confidential counseling services, and immediate post-incident psychological first aid.